Nursing students' perceptions of teaching effectiveness evaluations: A cross-sectional descriptive study - Maliheh Poorkiani; Nasser Al Salmi; Aisha Alshdefat; Zahra Sheikhalipour (Journal of Medical Education Development)
Background & Objective: While students' perceptions are rarely discussed in studies on student evaluations of teaching effectiveness, the majority concentrate on the features, validity, and reliability of the questionnaire used, the variables affecting students' ratings, and the proper assessment of teaching quality. Therefore, this study aims to look into how students at Sultan Qaboos University's College of Nursing perceive and behave when evaluating the faculty. Materials & Methods: This cross-sectional descriptive study was carried out in the academic year 2023–2024 during the summer and fall semesters. Two hundred thirty undergraduate students from Sultan Qaboos University's College of Nursing participated in the study. Convenience sampling was employed to gather data. A self-administered questionnaire was used to learn more about the students' opinions of Teaching Effectiveness (SETE). SPSS version 29 was used to analyze the data. The sample's demographics and the items about teaching effectiveness were described using frequency analysis. Furthermore, a correlational test was used to find relationships between SETE levels and demographic characteristics. Results: According to the study, the estimated presence of false information was 47.24%, and the mean perceived accuracy of evaluations was 50.78. A sizable percentage acknowledged providing or being aware of assessments that were either higher or lower than appropriate. There were different opinions about the evaluation process; 84.6% of respondents supported student evaluations, while 55.1% thought teachers read comments. With 76.1% of respondents considering false information to be cheating, ethical issues were raised. Statistical analyses revealed no significant relationships between sex and questionnaire responses, nor between evaluation perceptions, demographic characteristics, and Grade Point Average (GPA). Conclusion: The results show how complicated student opinions are regarding teacher assessments, particularly when it comes to truth and morality. The study calls for improvements in SETE processes to promote more reliable and reasonable evaluations.